Regional sectoral support: A review of the construction industry, SMEs and regional innovation strategies across Europe - Dick, James; Payne, David (International Journal of Strategic Property Management, 2010)
The performance of the EU construction industry in total makes a major impact on the European Community's economy, particularly on capital formation and employment. Small and Micro Enterprises account for 97% of businesses across the construction sector in the EU, a profile broadly reflected in the individual national and regional business base of members. This paper reviews the state of regional support for innovation and technology transfer in the Small Medium and Micro‐sized Enterprises (SME) sector of the Construction industry in the European Community. Results show that at the regional level, where most construction SMEs operate, there is a marked absence of focus on construction in either innovation support initiatives or business development services. Data on the construction industry at national and regional levels across Europe is not available in sufficient quality or detail for strategic decisions concerning this economically significant sector.First Published online: 18 Oct 2010